Demolding film

By using an addition curable silicone composition containing multiple alkenyl groups and rings in the release film, the recess and pinhole problems during the coating of ceramic slurry are solved, and The adhesion between the release layer and the polyester film is improved, the peeling force is reduced, and the yield is improved.

CN119136982APending Publication Date: 2024-12-13TOYOBO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380038336.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-04-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing release films are prone to depressions and pinholes when applied to ceramic slurry, resulting in increased yield and defective rates. The adhesion between the silicone release layer and the polyester film is poor, resulting in excessive peeling and peeling force. question.

Method used

A release film of an organic silicon composition containing an addition cured silicone type, which does not contain silicon atoms and nitrogen atoms, contains a resin containing a plurality of alkenyl groups and rings, and improves adhesion and density through hydrosilylation reaction. To avoid excessive peeling force.

Benefits of technology

Effectively reduce the degree of depression, inhibit the generation of depression, improve the adhesion between the release layer and the polyester film, avoid excessive peeling force, and improve the yield and use range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117267380000031
    Figure BDA0005117267380000031
  • Figure BDA0005117267380000041
    Figure BDA0005117267380000041
  • Figure BDA0005117267380000071
    Figure BDA0005117267380000071
Patent Text Reader

Abstract

A mold release film comprising a polyester film and a mold release layer, the mold release layer being a layer obtained by curing a silicone composition containing an addition-curable silicone, the silicone composition containing a resin that does not contain neither a silicon atom nor a nitrogen atom in a molecule, and that contains a plurality of alkenyl groups and a plurality of rings in the molecule.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to release films. Background Art

[0002] Conventionally, release films including a polyester film and a release layer have been used for various purposes, for example, not only for molding ceramic green sheets but also for manufacturing adhesive sheets, cover films, polymer films, optical lenses, and the like.

[0003] Various resins are used in the release layer of the release film according to the application of the release film, and silicone resins are often used in release films for applications requiring easy releasability. The release layer using silicone resin, i.e., silicone release layer, can be formed by cross-linking silicone resin having alkenyl group and silicone cross-linking agent having hydrosilyl group, for example.

[0004] When a liquid fluid (e.g., ceramic slurry, liquid composition for forming a polymer film) is applied to the silicone release layer, the end of the applied fluid partially retreats, resulting in uneven distribution of the fluid, i.e., depression. In addition, pinholes may also be generated. Depressions and pinholes lead to deterioration of the yield and defect rate.

[0005] In order to suppress the occurrence of sink marks, release films have been proposed in which a release layer is formed using a resin other than silicone resin (e.g., alkyd resin, acrylic resin, etc.) instead of silicone resin as a main component (see Patent Documents 1 and 2). However, such release films tend to have a heavier peeling force (i.e., a larger peeling force), so it is inevitable that such release films have a limit in the scope of use.

[0006] On the other hand, in order to solve the problem of the end of the applied ceramic slurry protruding, that is, the problem related to the depression, Patent Document 3 proposes a release film including a silicone release layer formed by using a phenyl-modified polydimethylsiloxane having an alkenyl group, but the structure of the phenyl-modified polydimethylsiloxane having an alkenyl group is limited in the sense of being a polydimethylsiloxane, so the adjustment range of the peeling force based on the phenyl-modified polydimethylsiloxane is also limited. Based on this, it has to be said that there is also a limit to the scope of use of the release film. In fact, in Patent Document 3, the use of the release film is limited to ceramic green sheet molding. Due to such a situation, a new method that can suppress the occurrence of depressions is sought.

[0007] However, in a release film having a polyester film and a silicone release layer disposed on the polyester film, if the polyester film and the silicone release layer have poor adhesion, the silicone constituting the silicone release layer may fall off from the polyester film. The fallen silicone may be transferred to an adherend (e.g., a ceramic green sheet) disposed or formed on the release layer, and thus the falling of the silicone release layer may sometimes lead to certain undesirable conditions (e.g., deterioration of the yield rate and defect rate). In order to suppress the falling of the silicone release layer, it is known to add an adhesion-imparting agent to the composition for forming the silicone release layer (see Patent Document 4), but a new method for improving the adhesion between the silicone release layer and the polyester film is still sought.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 5361589

[0011] Patent Document 2: Japanese Patent No. 5191220

[0012] Patent Document 3: Japanese Patent No. 5785706

[0013] Patent Document 4: Japanese Patent No. 6460183 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] An object of the present invention is to provide a release film which can reduce the degree of depression or suppress the occurrence of depression, improve the adhesion between the release layer and the polyester film, and prevent the peeling force from becoming too strong.

[0016] Solutions for solving problems

[0017] In order to solve this problem, the present invention has the following technical features [1]. [1]

[0019] A release film comprising a polyester film and a release layer.

[0020] The release layer is a layer formed by curing a silicone composition containing addition-curable silicone.

[0021] The silicone composition contains a resin having neither a silicon atom nor a nitrogen atom in the molecule and containing a plurality of alkenyl groups and a plurality of rings in the molecule.

[0022] The aforementioned rings are each independently at least one selected from the group consisting of a monovalent aromatic ring, a divalent aromatic ring, a monovalent aliphatic ring, and a divalent aliphatic ring.

[0023] Here, "addition curing silicone" is defined in this specification as containing polysiloxane containing hydrosilyl groups, ie, SiH groups. "Silicone composition" is defined in this specification as a composition that can be cured at least by hydrosilylation.

[0024] The present invention preferably also has the following technical features [2] and thereafter. [2]

[0026] The release film according to [1], wherein the alkenyl group is an allyl group. [3]

[0028] The release film according to [1] or [2], wherein the rings are each independently at least one selected from the group consisting of a phenylene group, a naphthylene group, a cyclopentylene group, and a cyclohexylene group. [4]

[0030] The release film according to any one of [1] to [3], wherein the resin contains a plurality of ester bonds in the molecule. [5]

[0032] The release film according to any one of [1] to [4], wherein the resin contains a plurality of structural units represented by the following formula (hereinafter sometimes referred to as "Formula C-U1") in the molecule.

[0033]

[0034] (A plurality of Xs are each independently at least one selected from the group consisting of a phenylene group, a naphthylene group, a cyclopentylene group, and a cyclohexylene group.)

[0035] In addition, in the release film of [5], the release film cited in [1] can be expressed in the following manner.

[0036] A release film comprising a polyester film and a release layer.

[0037] The release layer is a layer formed by curing a silicone composition containing addition-curable silicone.

[0038] The silicone composition contains a resin having neither a silicon atom nor a nitrogen atom in the molecule and containing a plurality of structural units represented by the above formula (ie, formula C-U1) in the molecule. [6]

[0040] The release film according to any one of [1] to [5], wherein the weight average molecular weight of the resin is 4,000 or more. [7]

[0042] The release film according to any one of [1] to [6], which is used for producing a ceramic green sheet. [8]

[0044] The release film according to any one of [1] to [7], wherein the resin contains a plurality of structural units represented by formula C-U1 in the molecule and a plurality of structural units represented by the following formula (hereinafter sometimes referred to as "formula C-U2").

[0045]

[0046] (A plurality of Ys are each independently at least one selected from the group consisting of a phenylene group, a naphthylene group, a cyclopentylene group, and a cyclohexylene group.)

[0047] Effects of the Invention

[0048] According to the present invention, it is possible to provide a release film which can reduce the degree of depression or suppress the occurrence of depression, improve the adhesion between the release layer and the polyester film, and prevent the peeling force from becoming too strong. DETAILED DESCRIPTION

[0049] <1. First>

[0050] The release film of this embodiment includes a polyester film and a release layer, wherein the release layer is a layer formed by curing a silicone composition containing addition-curable silicone, wherein the silicone composition contains a resin that contains neither silicon atoms nor nitrogen atoms in the molecule and contains multiple alkenyl groups and multiple rings in the molecule, and the rings are each independently at least one selected from the group consisting of a monovalent aromatic ring, a divalent aromatic ring, a monovalent aliphatic ring, and a divalent aliphatic ring.

[0051] In the release film of the present embodiment, the resin in the silicone composition contains a plurality of rings, and thus it is possible to reduce the degree of depression that may occur when a liquid fluid such as ceramic slurry is applied to the release film, or to suppress the occurrence of depression. This is believed to be because extremely fine depressions are formed on the surface of the release layer by the plurality of rings of the resin, and as a result, the adhesion energy (specifically, the adhesion energy obtained by measuring the slide angle using water. Hereinafter, sometimes referred to as "water adhesion energy") is improved. It is believed that the reason for this (specifically, the degree of depression can be reduced or the occurrence of depression can be suppressed by the plurality of rings of the resin) is also because the arrangement of the organic groups (such as methyl) of the polysiloxane in the silicone composition on the surface of the release layer is disordered by the plurality of rings of the resin, thereby improving the adhesion energy.

[0052] Furthermore, since the resin in the silicone composition contains a plurality of alkenyl groups, the adhesion between the release layer and the polyester film can be improved. This is believed to be because the resin in the silicone composition (specifically, the resin containing a plurality of alkenyl groups) is slightly biased toward the polyester film, and as a result, the alkenyl groups of the resin present near the polyester film can undergo an addition reaction (i.e., hydrosilylation) with the hydrosilyl groups in the silicone composition.

[0053] Furthermore, the resin in the silicone composition has neither a silicon atom nor a nitrogen atom in the molecule, that is, it is neither a melamine resin nor a silane coupling agent. Thus, according to the release film of this embodiment, the degree of sinking can be reduced, the generation of sinking can be suppressed, or the adhesion between the release layer and the polyester film can be improved without using a melamine resin or a silane coupling agent.

[0054] In addition, since the resin in the silicone composition is not a monomer but a resin, it is possible to avoid the peeling force when peeling the coating from the release film (for example, a liquid fluid such as a ceramic slurry is applied to the release film, dried, and solidified as needed to form a coating, and the peeling force when the coating is peeled from the release film) becoming too strong. That is, excessive re-peeling can be avoided. It is believed that the reason is that the resin in the silicone composition is not easy to move to the surface of the release layer and is not easy to precipitate on the surface of the release layer compared to the monomer. This is explained. Assuming that the monomer is used instead of the resin, the monomer is easy to move to the surface of the release layer and is easy to be exposed on the surface of the release layer. Therefore, the monomer sometimes causes excessive re-peeling. In contrast, in the release film of the present embodiment, since the resin in the silicone composition is not a monomer but a resin, it is not easy to move to the surface of the release layer and is not easy to precipitate on the surface of the release layer. Therefore, according to the release film of the present embodiment, the resin in the silicone composition is not a monomer but a resin, that is, a polymer, so excessive re-peeling can be avoided.

[0055] Hereinafter, embodiments of the present invention will be described in more detail.

[0056] <2. Release film>

[0057] The release film of this embodiment includes a polyester film and a release layer. Specifically, the release film of this embodiment includes a polyester film and a release layer provided on at least one surface of the polyester film.

[0058] An easy-adhesive layer, an antistatic layer, a smoothing layer, etc. can be provided between the release layer and the polyester film. In the present embodiment, even if an easy-adhesive layer, etc. are not provided, good adhesion can be easily obtained. That is, as a preferred mode, a release film formed by directly providing a release layer on the polyester film can be exemplified.

[0059] <2.1. Release layer>

[0060] The release layer is a layer formed by curing the silicone composition. Here, the silicone composition is a composition containing addition-curable silicone and can be cured at least by hydrosilylation. It should be noted that hydrosilylation is a reaction in which a polysiloxane containing a SiH group is added to an unsaturated bond such as a carbon-carbon double bond with the cleavage of the Si-H bond.

[0061] The addition-curable silicone contained in the silicone composition includes a polysiloxane containing a hydrosilyl group, i.e., a SiH group. The addition-curable silicone preferably includes, for example, a polysiloxane A containing two or more alkenyl groups in the molecule and a polysiloxane B containing two or more hydrosilyl groups in the molecule. That is, the silicone composition preferably includes a polysiloxane A containing two or more alkenyl groups in the molecule and a polysiloxane B containing two or more hydrosilyl groups in the molecule.

[0062] <2.1.1. Polysiloxane A>

[0063] The polysiloxane A may contain two or more alkenyl groups in the side chain and / or the terminal, and is preferably a polyorganosiloxane containing alkenyl groups at least in the side chain, and more preferably a polyorganosiloxane containing alkenyl groups only in the side chain. In addition, a copolymer containing a siloxane unit containing an alkenyl group and a dialkylsiloxane unit or an alkylphenylsiloxane unit is preferred because it exhibits mold release properties and is easy to adjust the amount of alkenyl groups in one molecule. The silicon atom at the terminal is preferably a trialkylsilane structure such as trimethylsilane.

[0064] As the alkenyl group, an alkenyl group having a carbon number of 2 or more and 10 or less can be cited. By containing such an alkenyl group, the strength of the release layer is excellent. The alkenyl group is preferably an alkenyl group having a carbon number of 2 or more and 8 or less, more preferably an alkenyl group having a carbon number of 2 or more and 6 or less, and particularly preferably a vinyl group or a hexenyl group. The silicon atom to which the alkenyl group is bonded may be bonded to a plurality of alkenyl groups, but preferably the alkenyl group is bonded to an alkyl group. As the alkyl group at this time, a methyl group or the like is preferably used.

[0065] Examples of the dialkylsiloxane unit contained in the polysiloxane A other than the alkenyl group-containing siloxane unit include a dimethylsiloxane unit, a phenylmethylsiloxane unit, and the like as preferred units.

[0066] Examples of the polysiloxane include polysiloxane represented by the following structural formula (1).

[0067]

[0068] In the above formula (1), l, m and n are integers greater than 0 (wherein m+n is greater than 2), and when l is greater than 1000 and less than 10000, and m+n is greater than 2 and less than 100, sufficient demolding properties are exhibited, and the crosslinking reaction proceeds appropriately, and the strength of the demolding layer is improved, so it is preferred. In addition, from the same viewpoint, (m+n) / (l+m+n+2) is preferably greater than 0.006 and less than 0.03, and more preferably greater than 0.01 and less than 0.024.

[0069] It should be noted that the above formula does not refer to a block copolymer, but only indicates that the total number of the respective units is l, m, and n. Therefore, the polysiloxane in the above formula may be a random copolymer or a block copolymer.

[0070] In this embodiment, as the polysiloxane A, one of the above-mentioned polysiloxanes may be used alone, or a polysiloxane containing two or more different alkenyl groups in one molecule may be used, or two or more polysiloxanes having different structures each containing different alkenyl groups may be used in combination.

[0071] The weight average molecular weight of polysiloxane A is preferably 300000 or more and 600000 or less, and particularly preferably 400000 or more and 550000 or less. The weight average molecular weight in this specification is a value calculated in terms of standard polystyrene measured by gel permeation chromatography (GPC).

[0072] When the weight average molecular weight of polysiloxane A is 300,000 or more, the release layer after crosslinking has an appropriate coating strength and can more effectively prevent the coating from falling off. When the weight average molecular weight is 600,000 or less, the planarity of the coating after drying becomes good.

[0073] <2.1.2. Polysiloxane B>

[0074] As long as polysiloxane B contains more than 2 hydrosilyl groups (a group formed by hydrogen atoms directly bonded to silicon atoms) in the side chain and / or the terminal, it is preferably a hydropolysiloxane containing hydrosilyl groups at least in the side chain, and more preferably a hydropolysiloxane containing hydrosilyl groups only in the side chain. In addition, it is a copolymer containing a siloxane unit containing a hydrosilyl group and a dialkylsiloxane unit or an alkylphenylsiloxane unit, which is preferred because it exhibits demoulding properties and is easy to adjust the amount of hydrosilyl groups in one molecule. The silicon atom directly bonded to the hydrogen atom can be directly bonded to multiple hydrogen atoms, but preferably the hydrogen atom is bonded to an alkyl group. As the alkyl group at this time, a methyl group is preferably used. The silicon atom at the terminal is preferably a trialkylsilane structure such as trimethylsilane.

[0075] As the dialkylsiloxane unit contained in the polysiloxane B, in addition to the siloxane unit containing a hydrosilyl group, a dimethylsiloxane unit, a phenylmethylsiloxane unit, etc. can be exemplified as a preferred unit.

[0076] Examples of the hydrogenated polysiloxane include polysiloxane represented by the following structural formula (2).

[0077]

[0078] In the above formula (2), o is an integer greater than 0, and p is an integer greater than 2. If o is greater than 0 and less than 120, p is greater than 2 and less than 120, and o+p is greater than 2 and less than 240, the crosslinking reaction proceeds appropriately, and the strength of the release layer is improved, which is preferred. In addition, from the same viewpoint, (p) / (o+p+2) is preferably greater than 0.3 and less than 1.

[0079] It should be noted that the above formulas do not indicate a block copolymer mode, but merely indicate that the total number of the respective units is o or p. Therefore, the hydrogenated polysiloxane in the above formulas may be a random copolymer or a block copolymer.

[0080] As the polysiloxane B, one of the above-mentioned hydrogenated polysiloxanes may be used alone, or two or more hydrogenated polysiloxanes having different structures such as different numbers of hydrogenated silyl groups in one molecule may be used in combination.

[0081] The weight average molecular weight of polysiloxane B is preferably 5000 or more and 100000 or less, and particularly preferably 7000 or more and 20000 or less. When the weight average molecular weight of polysiloxane B is 5000 or more, the release layer after crosslinking has a moderate coating strength, and can prevent the coating from falling off. In addition, when the weight average molecular weight is 100000 or less, the planarity of the coating after drying becomes good.

[0082] In the present embodiment, the above-mentioned polysiloxane A and polysiloxane B are preferably subjected to addition polymerization in the presence of a platinum catalyst described later, etc., to form a main component of the release layer. The addition polymerization mentioned here refers to the reaction of the functional group in the molecular terminal or molecular side chain of polysiloxane A represented by ~Si-CH=CH2 or ~Si-R-CH=CH2 and the functional group in the molecular terminal or molecular side chain of polysiloxane B represented by H-Si~ to become ~Si-CH2CH2-Si~ or ~Si-R-CH2CH2-Si~. Among them, the "~" in the above-mentioned functional group means that the molecules are further connected. When the reaction at this time is expressed as a reaction formula, it is as shown in the following formula. It should be noted that here, R represents an alkylene group with a carbon number of 1 or more and 8 or less.

[0083]

[0084] <2.1.3. Mixing mass ratio and total content of polysiloxane A and B>

[0085] In the silicone composition, the mixing mass ratio (B / A) of polysiloxane A to polysiloxane B can be appropriately set.

[0086] The total content of polysiloxane A and polysiloxane B is preferably 20% by mass or more, more preferably 40% by mass or more, further preferably 60% by mass or more, and further preferably 70% by mass or more in 100% by mass of the solid content in the silicone composition. On the other hand, the total content of polysiloxane A and polysiloxane B is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less, and further preferably 80% by mass or less.

[0087] <2.1.4. Resin containing neither silicon atoms nor nitrogen atoms in the molecule and containing multiple alkenyl groups and multiple rings in the molecule (resin C)>

[0088] The silicone composition contains a resin having neither silicon atoms nor nitrogen atoms in the molecule and containing multiple alkenyl groups and multiple rings in the molecule (hereinafter sometimes referred to as "resin C"). That is, the silicone composition contains a polymer having neither silicon atoms nor nitrogen atoms and containing multiple alkenyl groups and multiple rings.

[0089] Since resin C contains a plurality of rings, it is possible to reduce the degree of depression that may occur when a liquid fluid such as ceramic slurry is applied to a release film, or to suppress the occurrence of depression. This is believed to be because the multiple rings of resin C form extremely fine depressions and projections on the surface of the release layer, and as a result, adhesion energy (specifically, water adhesion energy) is improved. It is believed that the reason for this (specifically, the multiple rings of the resin can reduce the degree of depression or suppress the occurrence of depression) is that the multiple rings of resin C cause the arrangement of the organic groups (such as methyl) of the polysiloxane in the silicone composition to be disordered on the surface of the release layer, thereby improving adhesion energy.

[0090] Furthermore, since the resin C contains a plurality of alkenyl groups, the adhesion between the release layer and the polyester film can be improved. This is believed to be because the resin C is slightly localized toward the polyester film, and as a result, the alkenyl groups of the resin C present near the polyester film can undergo an addition reaction (i.e., hydrosilylation) with the hydrosilyl groups in the silicone composition.

[0091] Furthermore, since the resin C contains a plurality of alkenyl groups, the strength of the release layer (i.e., the amount of deformation until destruction) can be increased compared to a case where no alkenyl groups are contained. This is believed to be because the resin C contains a plurality of alkenyl groups, thereby enabling hydrosilylation and crosslinking of molecules (i.e., polymers) in the resin C.

[0092] Furthermore, the resin C has neither a silicon atom nor a nitrogen atom in the molecule, that is, it is neither a melamine resin nor a silane coupling agent. Thus, according to the release film of this embodiment, the degree of sinking can be reduced, the generation of sinking can be suppressed, or the adhesion between the release layer and the polyester film can be improved without using a melamine resin or a silane coupling agent.

[0093] In addition, since resin C is not a monomer but a resin, it is possible to avoid the peeling force when peeling the coating from the release film (for example, a liquid fluid such as a ceramic slurry is applied to the release film, dried, and solidified as needed to form a coating, and the peeling force when the coating is peeled from the release film) becoming too strong. That is, excessive re-peeling can be avoided. It is believed that the reason is that resin C is not easy to move to the surface of the release layer and is not easy to precipitate on the surface of the release layer compared to the monomer. This is explained. Assuming that a monomer is used instead of resin C, the monomer is easy to move to the surface of the release layer and is easy to be exposed on the surface of the release layer. Therefore, the monomer sometimes causes excessive re-peeling. In contrast, in the release film of the present embodiment, since resin C is not a monomer but a resin, it is not easy to move to the surface of the release layer and is not easy to precipitate on the surface of the release layer. Therefore, according to the release film of the present embodiment, resin C is not a monomer but a resin, so excessive re-peeling can be avoided.

[0094] The alkenyl groups contained in the molecule of the resin C are preferably each independently an alkenyl group having 2 to 6 carbon atoms. Examples of such alkenyl groups include vinyl groups and allyl groups. Among them, the products used in the examples described below are commercially available, and allyl groups are more preferred because they are generally easily available.

[0095] The rings contained in the molecules of resin C are each independently selected from at least one of the group consisting of a monovalent aromatic ring, a divalent aromatic ring, a monovalent aliphatic ring and a divalent aliphatic ring. As a monovalent aromatic ring, i.e., an aryl group, for example, phenyl and naphthyl (e.g., 1-naphthyl, 2-naphthyl) can be listed. As a divalent aromatic ring, i.e., an arylene group, for example, a phenylene group (e.g., o-phenylene, m-phenylene, p-phenylene) and a naphthylene group (e.g., 2,6-naphthylene) can be listed. As a monovalent aliphatic ring, i.e., a cycloalkyl group, for example, a cyclopentyl group and a cyclohexyl group can be listed. As a divalent aliphatic ring, i.e., a cycloalkylene group, for example, a cyclopentylene group (e.g., 1,2-cyclopentylene group, 1,3-cyclopentylene group) and a cyclohexylene group (e.g., 1,2-cyclohexylene group, 1,3-cyclohexylene group, 1,4-cyclohexylene group) can be listed. Among them, the products used in the embodiments described later are commercially available, and from the perspective of being basically easy to obtain, divalent aromatic rings and divalent aliphatic rings are preferably used. That is, the rings in the molecule are preferably each independently a divalent aromatic ring or a divalent aliphatic ring. In particular, for the reason that the rings are stable and can stably exert the effects of depression reduction and depression suppression, phenylene, naphthylene, cyclopentylene, and cyclohexylene are preferred, and phenylene and cyclohexylene are more preferred. That is, the rings in the molecule are preferably each independently selected from at least one of the group consisting of phenylene, naphthylene, cyclopentylene and cyclohexylene, and more preferably phenylene or cyclohexylene.

[0096] The resin C preferably contains a plurality of ester bonds, i.e., a plurality of ester groups, in the molecule. When the resin C contains ester bonds, electrostatic attraction can be generated between the ester bonds and polar groups (e.g., carboxyl groups, hydroxyl groups) present on the surface (e.g., corona discharge treated surface) of the polyester film, thereby further improving the adhesion between the release layer and the polyester film.

[0097] When describing a preferred example of the resin C specifically, the resin C preferably contains a plurality of structural units represented by the following formula (hereinafter, sometimes referred to as "formula C-U1") in the molecule.

[0098]

[0099] A plurality of Xs are each independently a divalent aromatic ring or a divalent aliphatic ring. A plurality of Xs are preferably each independently a phenylene, a naphthylene, a cyclopentylene or a cyclohexylene, more preferably a phenylene or a cyclohexylene. It is further preferred that a plurality of Xs are collectively a phenylene or collectively a cyclohexylene. It should be noted that, when a plurality of Xs are collectively a phenylene, the two ester bonds adjacent to the phenylene may be located at the ortho position, may be located at the meta position, or may be located at the para position.

[0100] When the resin C contains a plurality of structural units represented by the formula C-U1, the occurrence of sink marks can be further suppressed, and the adhesion between the release layer and the polyester film can be further improved.

[0101] The resin C may contain a plurality of structural units represented by the following formula (hereinafter, sometimes referred to as "formula C-U2") and structural units represented by formula C-U1 simultaneously in the molecule.

[0102]

[0103] A plurality of Ys are each independently a divalent aromatic ring or a divalent aliphatic ring. A plurality of Ys are preferably each independently a phenylene, a naphthylene, a cyclopentylene or a cyclohexylene, more preferably a phenylene or a cyclohexylene. It is further preferred that a plurality of Ys are collectively a phenylene or collectively a cyclohexylene. It should be noted that, when a plurality of Ys are collectively a phenylene, the two ester bonds adjacent to the phenylene may be located at the ortho position, may be located at the meta position, or may be located at the para position.

[0104] When the resin C contains the structural unit represented by the formula C-U1 and the structural unit represented by the formula C-U2 in the molecule, it is preferred that a plurality of Xs and a plurality of Ys are all phenylene groups, or a plurality of Xs and a plurality of Ys are all cyclohexylene groups.

[0105] The molar ratio of the structural unit represented by formula C-U1 to the structural unit represented by formula C-U2, specifically the number of moles of the structural unit represented by formula C-U1 / the number of moles of the structural unit represented by formula C-U2, can be 0.5 or more, 0.7 or more, or 0.8 or more. The molar ratio can be, for example, 1.5 or less, 1.3 or less, or 1.2 or less.

[0106] The resin C preferably includes a structure represented by the following formula (hereinafter, sometimes referred to as "Formula CP").

[0107]

[0108] A plurality of Xs are each independently a divalent aromatic ring or a divalent aliphatic ring. A plurality of Xs are preferably each independently a phenylene, a naphthylene, a cyclopentylene or a cyclohexylene, more preferably a phenylene or a cyclohexylene. It is further preferred that a plurality of Xs are collectively a phenylene or collectively a cyclohexylene. It should be noted that, when a plurality of Xs are collectively a phenylene, the two ester bonds adjacent to the phenylene may be located at the ortho position, may be located at the meta position, or may be located at the para position.

[0109] A plurality of Ys are each independently a divalent aromatic ring or a divalent aliphatic ring. A plurality of Ys are preferably each independently a phenylene, a naphthylene, a cyclopentylene or a cyclohexylene, more preferably a phenylene or a cyclohexylene. It is further preferred that a plurality of Ys are collectively a phenylene or collectively a cyclohexylene. It should be noted that, when a plurality of Ys are collectively a phenylene, the two ester bonds adjacent to the phenylene may be located at the ortho position, may be located at the meta position, or may be located at the para position.

[0110] It is particularly preferred that a plurality of Xs and a plurality of Ys are all phenylene groups, or a plurality of Xs and a plurality of Ys are all cyclohexylene groups.

[0111] m is an integer greater than 2, and n is also an integer greater than 2. When the structure represented by formula CP includes the structural unit represented by formula C-U1 and the structural unit represented by formula C-U2, the molar ratio of the structural unit represented by formula C-U1 to the structural unit represented by formula C-U2 (specifically, the molar number of the structural unit represented by formula C-U1 / the molar number of the structural unit represented by formula C-U2) can be 0.5 or more, 0.7 or more, or 0.8 or more. This molar ratio can be, for example, less than 1.5, less than 1.3, or less than 1.2.

[0112] It should be noted that the formula CP does not refer to the mode of block copolymers, they just represent that the total count of each unit is m, n. Therefore, the polymer containing the structure shown in the formula CP can be a random copolymer or a block copolymer. Among them, a random copolymer is preferred.

[0113] As a preferred example of resin C, diallyl phthalate resin and diallyl cyclohexane resin can be listed. If resin C is diallyl phthalate resin or diallyl cyclohexane resin, the generation of depression can be further suppressed, and the adhesion between the release layer and the polyester film can be further improved. As diallyl phthalate resin, for example, a resin containing multiple structural units represented by formula C-U1 in the molecule and X is a phenylene group can be listed. As diallyl phthalate resin, a resin containing a structure represented by formula CP and X and Y are both phenylene groups can also be listed. As a commercial product of diallyl phthalate resin, for example, DAP-K manufactured by OSAKA SODA CO., LTD., ISODAP manufactured by OSAKA SODACO., LTD., and DAP-A manufactured by OSAKA SODA CO., LTD. can be listed. As the diallyl cyclohexane resin, for example, a resin containing a plurality of structural units represented by the formula C-U1 in the molecule and X being a cyclohexylene group can be cited. As the diallyl phthalate resin, a resin containing a structure represented by the formula CP and X and Y being both cyclohexylene groups can also be cited. As a commercially available product of the diallyl cyclohexane resin, for example, AD-032 manufactured by OSAKA SODA CO., LTD. can be cited.

[0114] The diallylcyclohexane resin is preferably a polymer including a structure represented by the following formula (hereinafter, sometimes referred to as “Formula C1”).

[0115]

[0116] In formula C1, m is an integer greater than 2, and n is also an integer greater than 2. When the structure represented by formula C1 includes the structural unit shown on the left (i.e., an example of the structural unit represented by formula C-U1) and the structural unit shown on the right (i.e., an example of the structural unit represented by formula C-U2), the molar ratio of the former structural unit to the latter structural unit can be 0.5 or more, 0.7 or more, or 0.8 or more. The molar ratio can be, for example, less than 1.5, less than 1.3, or less than 1.2.

[0117] It should be noted that formula C1 does not refer to a block copolymer, but only indicates that the total number of each unit is m, n. Therefore, the polymer containing the structure shown in formula C1 can be a random copolymer or a block copolymer. Among them, a random copolymer is preferred.

[0118] The diallyl phthalate resin is preferably a polymer including a structure represented by the following formula (hereinafter, sometimes referred to as “Formula C2”).

[0119]

[0120] In formula C2, m is an integer greater than 2, and n is also an integer greater than 2. When the structure represented by formula C2 includes the structural unit shown on the left (i.e., an example of the structural unit represented by formula C-U1) and the structural unit shown on the right (i.e., an example of the structural unit represented by formula C-U2), the molar ratio of the former structural unit to the latter structural unit can be 0.5 or more, 0.7 or more, or 0.8 or more. The molar ratio can be, for example, less than 1.5, less than 1.3, or less than 1.2.

[0121] It should be noted that formula C2 does not refer to the mode of block copolymers, they just represent the total number of their respective units as m, n. Therefore, the polymer containing the structure shown in formula C2 can be a random copolymer or a block copolymer. Among them, a random copolymer is preferred.

[0122] The diallyl phthalate resin is preferably a polymer including a structure represented by the following formula (hereinafter, sometimes referred to as “Formula C3”).

[0123]

[0124] In formula C3, m is an integer of 2 or more.

[0125] The polymer including the structures represented by Formula C1, Formula C2, and Formula C3 may further include other structural units in addition to the structural units represented by these formulas.

[0126] The weight average molecular weight of resin C is preferably 4000 or more, more preferably 5000 or more, further preferably 10000 or more, further preferably 15000 or more. When it is 4000 or more, it is possible to further avoid the peeling force when the coating is peeled off from the release film (for example, a liquid fluid such as a ceramic slurry is applied to the release film, dried, and solidified as needed to form a coating, and the peeling force when the coating is peeled off from the release film) becoming too strong. It is believed that the reason is that if the weight average molecular weight is 4000 or more, resin C is less likely to move to the surface of the release layer and is less likely to precipitate on the surface of the release layer. On the other hand, the weight average molecular weight of resin C can be, for example, less than 200000, less than 100000, less than 80000, or less than 60000. It should be noted that the weight average molecular weight in this specification is a value converted to standard polystyrene measured by gel permeation chromatography (GPC).

[0127] When the total amount of polysiloxane A and polysiloxane B is set to 100 parts by mass, the content of resin C in the silicone composition is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and more preferably 20 parts by mass or more. If it is 5 parts by mass or more, it is possible to further reduce the degree of depression, further suppress the generation of depression, or further improve the adhesion between the release layer and the polyester film. On the other hand, when the total amount of polysiloxane A and polysiloxane B is set to 100 parts by mass, the content of resin C is preferably 80 parts by mass or less, more preferably 60 parts by mass or less, more preferably 40 parts by mass or less, and more preferably 30 parts by mass or less. If it is 80 parts by mass or less, it is possible to further avoid the peeling force when the coating is peeled off from the release film (for example, a liquid fluid such as a ceramic slurry is applied to the release film, dried, and solidified as needed to form a coating, and the peeling force when the coating is peeled off from the release film) becomes too strong.

[0128] <2.1.5. Catalyst>

[0129] The silicone composition preferably further contains a catalyst. The catalyst is not particularly limited as long as it can promote the curing reaction of the silicone composition, but a platinum group metal compound is preferred.

[0130] Examples of platinum group metal compounds include fine particulate platinum, fine particulate platinum adsorbed on a carbon powder carrier, chloroplatinic acid, alcohol-modified chloroplatinic acid, olefin complexes of chloroplatinic acid, palladium, rhodium, etc. By including the above catalyst in the silicone composition, the curing reaction of the silicone composition can be more efficiently performed.

[0131] The content of the catalyst in the silicone composition is preferably about 1 ppm or more and 1000 ppm or less relative to the total amount of polysiloxane A and polysiloxane B.

[0132] <2.1.6. Photopolymerization initiator>

[0133] The silicone composition preferably further contains a photopolymerization initiator. In particular, when the content of resin C is high (for example, when the total amount of polysiloxane A and polysiloxane B is set to 100 parts by mass, when resin C is 50 parts by mass or more), it is preferred to contain a photopolymerization initiator. The reason is believed to be that catalysts such as platinum group metal compounds exist compatibly with polysiloxane A and polysiloxane B, so the catalyst may not be able to act efficiently on the self-crosslinking reaction of resin C. As the photopolymerization initiator, for example, alkyl phenyl ketone-based photopolymerization initiators can be listed. Specifically, Omnirad185, Omnirad907, etc. can be listed.

[0134] The content of the photopolymerization initiator in the silicone composition is preferably about 1 ppm or more and 1000 ppm or less relative to the total amount of all solid components other than the photopolymerization initiator.

[0135] <2.1.7. Other ingredients>

[0136] The silicone composition may contain, in addition to the above-mentioned components, a reaction inhibitor, a solvent, a silicone resin having no reactive functional group, an antistatic agent, a melamine resin, a silane coupling agent, and the like.

[0137] <2.1.8. Thickness of release layer>

[0138] The thickness of the release layer is preferably 0.005 μm or more, more preferably 0.01 μm or more. When it is 0.005 μm or more, it can effectively function as a release layer. On the other hand, the thickness of the release layer is preferably 0.5 μm or less, more preferably 0.1 μm or less, and further preferably 0.05 μm or less. When it is 0.5 μm or less, it can suppress the occurrence of damage in the release layer, that is, cohesive failure.

[0139] <2.2. Polyester film>

[0140] In the present embodiment, the polyester film used as the base film (hereinafter sometimes referred to as base) is a film containing polyester as a resin component, and preferably a film containing the largest amount of polyester in the resin component (eg 90 mass % or more).

[0141] The polyester constituting the polyester film is not particularly limited, and may be a polyester formed by film-forming a polyester generally used as a base material for a release film. Preferably, it is a crystalline linear saturated polyester containing an aromatic dibasic acid component and a diol component, and more preferably, polyethylene terephthalate, polyethylene 2,6-naphthalate, polybutylene terephthalate, polytrimethylene terephthalate, or a copolymer containing the constituent components of these resins as a main component.

[0142] Particularly preferred is a polyester film formed from polyethylene terephthalate. In polyethylene terephthalate, the repeating unit of ethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and other dicarboxylic acid components and glycol components may be copolymerized in small amounts. For example, from the viewpoint of cost, it is preferably made only from terephthalic acid and ethylene glycol. In addition, known additives such as antioxidants, light stabilizers, ultraviolet absorbers, crystallizing agents, etc. may be added to the polyester film. From the reasons such as high elastic modulus in both directions, the polyester film is preferably a biaxially oriented polyester film.

[0143] The intrinsic viscosity of the polyethylene terephthalate film is preferably 0.50 dl / g or more and 0.70 dl / g or less, and more preferably 0.52 dl / g or more and 0.62 dl / g or less. When the intrinsic viscosity is 0.50 dl / g or more, the frequency of fracture in the stretching process can be reduced. On the other hand, if it is 0.70 dl / g or less, the cutting property when cutting into a specified product width is good, so the frequency of dimensional defects can be reduced. By the way, the raw material pellets are preferably fully vacuum dried.

[0144] In addition, in this specification, when it is described simply as "polyester film", it may mean the polyester film which consists of the surface layer A and the surface layer B (laminated).

[0145] The method for producing the polyester film is not particularly limited, and a conventionally commonly used method can be used. For example, the polyester is melted and extruded into a film by an extruder, and cooled by a rotating cooling drum to obtain an unstretched film, and the unstretched film is uniaxially or biaxially stretched to obtain a polyester film. A biaxially stretched film can be obtained by a method in which a uniaxially stretched film in the longitudinal or transverse direction is biaxially stretched in the transverse direction or longitudinal direction in sequence, or a method in which an unstretched film is biaxially stretched in the longitudinal and transverse directions simultaneously.

[0146] The stretching temperature during stretching of the polyester film is preferably set to be equal to or higher than the secondary transition point (Tg) of the polyester. It is preferred to stretch the film by 1 to 8 times, particularly 2 to 6 times, in each of the longitudinal and transverse directions.

[0147] The thickness of the polyester film is preferably 12 μm or more and 50 μm or less, more preferably 15 μm or more and 38 μm or less, and more preferably 19 μm or more and 33 μm or less. When the thickness of the film is 12 μm or more, it is preferred that the film will not be deformed by heat during film production, processing, and molding. On the other hand, if the thickness of the film is 50 μm or less, the amount of film discarded after use will not increase extremely, which is preferred in terms of reducing environmental load.

[0148] The polyester film may be a single layer or a multilayer of two or more layers. For example, the polyester film may include a surface layer A substantially free of particles having a particle size of 1.0 μm or more and a surface layer B containing particles. Preferably, the surface layer A substantially does not contain inorganic particles having a particle size of 1.0 μm or more.

[0149] In this embodiment, particles having a particle size of less than 1.0 μm and 1 nm or more may exist in the surface layer A. Since the surface layer A does not substantially contain particles having a particle size of 1.0 μm or more, such as inorganic particles, it is possible to reduce the transfer of particle shapes in the substrate to the resin sheet and the generation of defects.

[0150] In one embodiment, the surface layer A also does not contain particles having a particle diameter of less than 1.0 μm, thereby more effectively preventing the particle shape in the substrate from being transferred to the resin sheet and causing a problem.

[0151] In one embodiment, the polyester film substrate is preferably a laminated film having a surface layer A substantially free of inorganic particles on at least one surface. This can more effectively prevent the particle shape in the substrate from being transferred to the resin sheet to cause a problem.

[0152] For example, the surface layer A substantially not containing particles having a particle size of less than 1.0 μm is preferably a mode in which the surface layer A substantially not containing particles having a particle size of 1.0 μm or more is also preferably.

[0153] Here, in the present invention, "substantially free of particles" means, for example, in the case of inorganic particles smaller than 1.0 μm, the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when the inorganic elements are quantified by fluorescent X-ray analysis. This is because, even if particles are not actively added to the film, sometimes contaminant components from foreign matter, dirt attached to the production line and equipment in the manufacturing process of the raw resin or film will be peeled off and mixed into the film. In addition, "substantially free of particles with a particle size of 1.0 μm or more" means that particles with a particle size of 1.0 μm or more are actively free of particles.

[0154] In the case of a laminated polyester film having a multilayer structure including two or more layers, it is preferred that a surface layer B which may contain inorganic particles and the like is provided on the opposite side of a surface layer A which does not substantially contain inorganic particles.

[0155] As a laminated structure, if the layer on one side of the coating release layer is set to the A layer, the layer on the opposite side is set to the B layer, and the core layer other than them is set to the C layer, the layer structure in the thickness direction can list laminated structures such as release layer / A / B or release layer / A / C / B. Of course, the C layer can also be a multilayer structure. In addition, inorganic particles may not be contained in the surface layer B. At this time, in order to give the slipperiness for winding the film into a roll, it is preferred that a coating layer D comprising at least inorganic particles and a binder is provided on the surface layer B.

[0156] In the polyester film substrate of the present invention, from the viewpoint of the slipperiness of the film and the ease of air discharge, the surface layer B on the opposite side of the surface to which the release layer is applied preferably contains inorganic particles, and silica particles and / or calcium carbonate particles are particularly preferably used. The content of the inorganic particles contained in the surface layer B preferably contains 5000 ppm or more and 15000 ppm or less based on the total amount of the inorganic particles.

[0157] At this time, the regional surface average roughness (Sa) of the film of surface layer B is preferably the scope of more than 1nm and less than 40nm. More preferably, the scope of more than 5nm and less than 35nm. In the case where the total amount of silicon dioxide particles and / or calcium carbonate particles is more than 5000ppm and Sa is more than 1nm, when the film is rolled into a roll, air can be uniformly escaped, and the winding state is good and the planarity is good, which is suitable for the manufacture of ultra-thin layer ceramic green sheets. In addition, in the case where the total amount of silicon dioxide particles and / or calcium carbonate particles is less than 15000ppm and Sa is less than 40nm, it is not easy to produce the aggregation of lubricants, and it is impossible to form thick protrusions, so the quality is stable when manufacturing the ceramic green sheets of ultra-thin layers, which is preferred.

[0158] As the particles contained in the above-mentioned B layer, in addition to silicon dioxide and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles, etc. can also be used. From the viewpoint of transparency and cost, silicon dioxide particles and / or calcium carbonate particles are more preferably used. In addition, as other inorganic particles that can be used, aluminum oxide-silicon dioxide composite oxide particles, hydroxyapatite particles, etc. can be listed. In addition, as heat-resistant organic particles, cross-linked polyacrylic acid particles, cross-linked polystyrene particles, benzoguanamine particles, etc. can be listed. In addition, when using silicon dioxide particles, porous colloidal silica is preferred, and when using calcium carbonate particles, from the viewpoint of preventing the lubricant from falling off, it is preferably a light calcium carbonate that has been surface-treated with a high molecular compound of a polyacrylic acid.

[0159] The average particle size of the inorganic particles added to the surface layer B is preferably 0.1 μm or more and 2.0 μm or less, and particularly preferably 0.5 μm or more and 1.0 μm or less. When the average particle size of the inorganic particles is 0.1 μm or more, the slip property of the release film is good and preferred. In addition, if the average particle size is 2.0 μm or less, it will not adversely affect the smoothness of the surface of the release layer, so pinholes will not be generated in the ceramic green sheet, so it is preferred. It should be noted that the method for determining the average particle size of the particles can be carried out by the following method: observe the particles of the cross section of the processed film with a scanning electron microscope, observe 100 particles, and take the average value as the average particle size. As long as the purpose of the present invention is met, the shape of the particles is not particularly limited, and spherical particles and amorphous non-spherical particles can be used. The particle size of amorphous particles can be calculated as an equivalent circle diameter. The equivalent circle diameter is the value obtained by dividing the area of ​​the observed particles by the pi (π), calculating the square root and multiplying it by 2 times.

[0160] In the surface layer A, which is a layer on the side where the release layer is provided, it is preferred not to use recycled raw materials or the like in order to prevent the incorporation of inorganic particles such as lubricants from the viewpoint of reducing pinholes.

[0161] The thickness ratio of the surface layer A as the layer on the side where the release layer is provided is preferably 20% or more and 50% or less of the thickness of the total layers of the substrate film. If it is 20% or more, it is not easy to be affected by the particles contained in the surface layer B etc. from the inside of the film, and the regional surface average roughness Sa is easy to meet the above range, so it is preferred. If it is 50% or less of the thickness of the total layers of the substrate film, the use ratio of the recycled raw materials in the surface layer B can be increased, and the environmental load is small, which is preferred.

[0162] In addition, from the viewpoint of economic efficiency, the layer other than the surface layer A (the surface layer B or the intermediate layer C) may use 50% by mass or more and 90% by mass or less of recycled raw materials of film scraps or plastic bottles. In this case, the type, amount, particle size and regional surface average roughness (Sa) of the lubricant contained in the B layer also preferably satisfy the above ranges.

[0163] In addition, in order to improve the adhesion of the release layer to be applied later, prevent static electricity, etc., a coating layer D can be set on the surface of the surface layer A and / or the surface layer B before stretching in the film forming process or after uniaxial stretching, and corona treatment can also be performed.

[0164] In the case where the surface layer B does not contain particles, it is also preferred that the surface layer B has lubricity by means of a coating layer D containing particles. The means for providing the coating layer D is not particularly limited, and it is preferably provided by a so-called online coating method in which the coating is applied during the film formation of the polyester film. In addition, in the case where a coating layer D having lubricity is provided on the surface of the side of the polyester film on which the release layer is not laminated, the polyester film does not need to include the surface layers A and B, and may be composed of a single-layer polyester film substantially free of inorganic particles.

[0165] The average surface roughness (Sa) of the surface layer B is preferably 40 nm or less, more preferably 35 nm or less, and further preferably 30 nm or less. In addition, when the surface layer B or the surface of the side of the single-layer polyester film on which the release layer is not laminated is made slippery by using the coating layer D, the Sa of the surface is set to the value obtained by measuring the surface laminated with the coating layer D, and is preferably in the same range as the average surface roughness (Sa) of the surface layer B.

[0166] It is preferred that the polyester film contain at least a binder resin and particles in the coating layer D on the surface on which the release layer is not laminated.

[0167] (Binder resin of coating layer D)

[0168] There is no particular limitation on the binder resin constituting the slippery coating layer. Specific examples of polymers include polyester resins, acrylic resins, polyurethane resins, polyvinyl resins (polyvinyl alcohol, etc.), polyalkylene glycols, polyalkylene imines, methyl cellulose, hydroxy cellulose, starches, etc. Among them, from the viewpoint of particle retention and adhesion, polyester resins, acrylic resins, and polyurethane resins are preferably used. In addition, in consideration of compatibility with polyester film, polyester resins are particularly preferred. In order to achieve solubility and dispersibility in solvents, and then adhesion to substrate films and other layers, the polyester of the binder is preferably a copolyester. It should be noted that the polyester resin can also be polyurethane-modified. In addition, as other preferred binder resins constituting the slippery coating layer on the polyester substrate film, polyurethane resins can be listed. As polyurethane resins, polycarbonate polyurethane resins can be listed. Furthermore, polyester resins and polyurethane resins can be used in combination, and the above-mentioned other binder resins can also be used in combination.

[0169] (Crosslinking agent for coating layer D)

[0170] In order to form a crosslinked structure in the slippery coating layer, the slippery coating layer may be formed by including a crosslinking agent. By containing a crosslinking agent, the adhesion under high temperature and high humidity can be further improved. As specific crosslinking agents, urea systems, epoxy systems, melamine systems, isocyanate systems, oxazoline systems, carbodiimide systems, aziridine systems, etc. can be listed. In addition, in order to promote the crosslinking reaction, catalysts, etc. can be appropriately used as needed.

[0171] (Particles in coating layer D)

[0172] In order to impart slipperiness to the surface, the slippery coating layer preferably contains lubricant particles. The particles may be inorganic particles or organic particles, and are not particularly limited. Examples thereof include (1) inorganic particles of silica, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, zirconium oxide, titanium dioxide, satin white, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, hydrohalogenite, calcium carbonate, magnesium carbonate, calcium phosphate, magnesium hydroxide, and barium sulfate; and (2) organic particles of acrylic or methacrylic acid, vinyl chloride, vinyl acetate, nylon, styrene / acrylic, styrene / butadiene, polystyrene / acrylic, polystyrene / isoprene, polystyrene / isoprene, methyl methacrylate / butyl methacrylate, melamine, polycarbonate, urea, epoxy, urethane, phenol, diallyl phthalate, and polyester. In order to impart appropriate slip properties to the coating layer, silica is particularly preferably used.

[0173] The average particle size of the particles is preferably 10 nm or more, more preferably 20 nm or more, and further preferably 30 nm or more. When the average particle size of the particles is 10 nm or more, the particles are less likely to aggregate and the slip properties can be ensured, which is preferred.

[0174] The average particle size of the particles is preferably 1000 nm or less, more preferably 800 nm or less, and further preferably 600 nm or less. When the average particle size of the particles is 1000 nm or less, transparency is maintained and the particles do not fall off, which is preferred.

[0175] In addition, for example, small particles with an average particle size of about 10 nm or more and about 270 nm or less and large particles with an average particle size of about 300 nm or more and about 1000 nm or less are mixed, while maintaining the surface average roughness (Sa) of the region described later, the maximum protrusion height (RP) is small, and the average length (RSm) of the roughness curve element is reduced, and it is also preferred to take into account the sliding property and smoothness. It is particularly preferred to use small particles with an average particle size of about 30 nm or more and about 250 nm or less and large particles with an average particle size of about 350 nm or more and about 600 nm or less. In the case of mixing small particles and large particles, it is preferred to make the mass content of small particles greater than the mass content of large particles relative to the entire solid component of the coating layer.

[0176] <2.3. Formation of release layer>

[0177] In the present invention, the method for forming the release layer is not particularly limited, and the following method can be used: a coating liquid in which a release compound is dissolved or dispersed is spread on one surface of the polyester film of the substrate by coating, etc., and the solvent is removed by drying, etc., and then the coating liquid is cured. A method of curing by heat while removing the solvent can also be used.

[0178] When the release layer of the present invention is coated on the substrate film by solution coating, the drying temperature of the solvent drying is preferably above 50°C and below 120°C, more preferably above 60°C and below 100°C. The drying time is preferably below 30 seconds, more preferably below 20 seconds. After the solvent is dried, it is preferably irradiated with active energy rays to cause the curing reaction to proceed. As the active energy rays used at this time, ultraviolet rays, electron beams, X-rays, etc. can be used, but ultraviolet rays are easier to use and are therefore preferred. As the amount of ultraviolet rays irradiated, it is preferably 30 mJ / cm in terms of light intensity. 2 Above and 300mJ / cm 2 Below, more preferably 30mJ / cm 2 Above and 200mJ / cm 2 Below. By setting it to 30mJ / cm 2 On the other hand, by setting the curing rate to 300 mJ / cm 2 Next, the speed during processing can be improved, so that the release film can be produced economically.

[0179] The surface tension of the coating liquid when applying the release layer is not particularly limited, but is preferably 30 mN / m or less. By adjusting the surface tension to the above, the coating properties after coating are improved, and the unevenness of the coating film surface after drying can be reduced.

[0180] As a coating method for the above-mentioned coating liquid, any known coating method can be applied, for example, a conventionally known method such as a gravure coating method, a roll coating method such as a reverse coating method, a rod coating method such as a wire bar, a die coating method, a spray coating method, and an air knife coating method can be used.

[0181] <2.4. Physical properties of release film>

[0182] The water adhesion energy of the release layer surface, that is, the adhesion energy obtained by measuring the slide angle using water, is preferably 7.0 mJ / m 2 More preferably, 7.5 mJ / m 2 The water adhesion energy on the surface of the release layer can be, for example, 8.0 mJ / m 2 Above, 8.1mJ / m 2 Above, 8.2mJ / m 2 The water adhesion energy on the surface of the release layer is measured by the method described in Examples described later.

[0183] The change ratio of wipe-off after wet heat treatment (i.e., peeling force of wiped portion / peeling force of unwiped portion) as an indicator of adhesion is preferably less than 5 times, more preferably less than 4 times, and further preferably less than 3 times. The change ratio of wipe-off after wet heat treatment is measured by the method described in the examples described later.

[0184] After the release film is attached to the pressure-sensitive adhesive tape, the peel strength measured by a T-type peeling method at 23° C. and 0.3 m / min is, for example, preferably 100 mN / 50 mm or less, more preferably 95 mN / 50 mm or less. The peel strength is measured by the method described in Examples below.

[0185] These physical properties (specifically, water adhesion, change ratio of wiping off after wet heat treatment, and peeling force) can be appropriately set according to the application of the release film. Of course, these physical property values ​​may also deviate from the above-mentioned preferred numerical ranges.

[0186] <2.5. Application of release film>

[0187] The use of the release film of the present embodiment is not particularly limited. The release film can be used not only for the manufacture of ceramic green sheets, but also for the manufacture of, for example, adhesive sheets, cover films, polymer films, optical lenses, multilayer printed wiring boards, etc. In the manufacture of ceramic green sheets, for example, the release film of the present embodiment can be used to manufacture ceramic green sheets for stacked ceramic capacitors. That is, the release film of the present embodiment can be used to manufacture stacked ceramic capacitors. In the manufacture of multilayer printed wiring boards, for example, when a multilayer printed wiring board is manufactured by a lamination method, the release film of the present embodiment can be used as a supporting film for supporting an insulating layer. The release film of the present embodiment can be particularly suitable for the manufacture of ceramic green sheets.

[0188] The ceramic green sheet can be produced by applying a ceramic slurry for forming a ceramic green sheet to the release layer of the release film of the present embodiment and drying the ceramic slurry.

[0189] The ceramic green sheet may contain an inorganic compound. Examples of the inorganic compound include metal particles, metal oxides, and minerals. Examples thereof include calcium carbonate, silica particles, aluminum particles, and barium titanate particles.

[0190] The ceramic green sheet may contain a resin component. The resin component may be appropriately selected according to the intended use. Examples of the resin component include polyvinyl butyral resins.

[0191] The thickness of the ceramic green sheet can be, for example, 0.2 μm or more and 1.0 μm or less.

[0192] In addition, generally, a multilayer ceramic capacitor includes a rectangular parallelepiped ceramic body. Inside the ceramic body, a first internal electrode and a second internal electrode are alternately arranged along the thickness direction. The first internal electrode is exposed at the first end face of the ceramic body. A first external electrode is arranged on the first end face. The first internal electrode is electrically connected to the first external electrode at the first end face. The second internal electrode is exposed at the second end face of the ceramic body. A second external electrode is arranged on the second end face. The second internal electrode is electrically connected to the second external electrode at the second end face.

[0193] A stacked ceramic capacitor can be manufactured, for example, in the following steps. First, using the release film of the present embodiment as a carrier film, a ceramic slurry for constituting a ceramic body is applied and dried. The thickness of the ceramic green sheet is required to be an extremely thin product of not less than 0.2 μm and not more than 1.0 μm. A conductive layer for constituting the first or second internal electrode is printed on the coated and dried ceramic green sheet. The ceramic green sheet, the ceramic green sheet printed with the conductive layer for constituting the first internal electrode, and the ceramic green sheet printed with the conductive layer for constituting the second internal electrode are appropriately stacked and pressed to obtain a mother stack. The mother stack is divided into a plurality of pieces to produce an unprocessed ceramic body. The ceramic body is obtained by firing the unprocessed ceramic body. Thereafter, by forming the first and second external electrodes, the stacked ceramic capacitor can be completed.

[0194] Example

[0195] The following examples and comparative examples are given to more specifically illustrate the present invention. It should be noted that in the present invention, physical properties are measured or evaluated by the following methods. Hereinafter, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0196] <Methods for measuring various physical properties>

[0197] (Weight average molecular weight)

[0198] The sample solution adjusted to a sample concentration of 0.2% was filtered through a 0.2 μm membrane filter and analyzed by gel permeation chromatography (GPC) under the following conditions to determine the weight average molecular weight. The molecular weight was calculated in terms of standard polystyrene.

[0199] Device: TOSOH HLC-8320GPC

[0200] Chromatographic column: TSKgel SuperHM-H×2+TSKgel SuperH2000 (TOSOH)

[0201] Solvent: Chloroform 100%

[0202] Flow rate: 0.6ml / min

[0203] Concentration: 0.2%

[0204] Injection volume: 20μl

[0205] Temperature: 40℃

[0206] Detector: RI

[0207] (Thickness of release layer)

[0208] The release film was embedded with resin and ultra-thin sliced ​​using an ultramicrotome. Then, a JEM2100 transmission electron microscope manufactured by JEOL was used to observe the cross section, and the film thickness of the release layer was measured from the observed TEM image. In the case where the thickness was too thin to be accurately evaluated by cross-sectional observation, the Si intensity was measured using a fluorescent X-ray device (ZSXPRIMUSII manufactured by Rigaku), and the coating amount was calculated using a standard curve method.

[0209] (Tape peeling force of release layer)

[0210] The adhesive layer of 50 mm wide acrylic adhesive tape No. 31B (manufactured by Nitto Denko Corporation) was attached to the release layer surface of the release film using a hand roller to prepare a laminate. After the laminate was stored at 23° C. for 24 hours, it was stretched at a speed of 0.3 m / min using a tensile tester in a T-type peeling method with the release film in the downward direction and the adhesive tape in the upward direction, and the peeling force (mN / 50 mm) measured in an atmosphere of 23° C. was recorded.

[0211] (Scraping adhesion of release layer after wet heat treatment (wipe off after wet heat treatment))

[0212] The release film was stored at 60°C and 90% RH for 3 days. Next, a pearl paper (TOYOBO ESTER Film P4255-35 manufactured by Toyobo Co., Ltd.) was attached to the load head (i.e., friction material) of a Gakujuji friction tester (manufactured by Yamaguchi Science Industry Co., Ltd.) via gauze (Hakujuji Gauze manufactured by White Cross Co., Ltd.), and then the load head with the pearl paper was subjected to a load of 200 gf / 25 mm. 2 (5mm×5mm) (i.e., 0.0785MPa) was reciprocated 10 times to rub the release layer of the release film. An adhesive tape (Nitto-31B manufactured by Nitto Denko) was pasted on the rubbed and unrubbed parts of the release layer. After storage for 20 hours, T-type peeling was performed at a speed of 300mm / min using Autograph to measure the peeling force. The variation ratio (i.e., peeling force of the rubbed part / peeling force of the unrubbed part) was calculated from the peeling force of the rubbed part and the peeling force of the unrubbed part, and the judgment was made as follows. The variation ratio is shown in Table 1 together with the judgment results. The smaller the variation ratio, the better the adhesion (this can also be called adhesion durability) between the release layer and the polyester film.

[0213] ○: The peeling force of the rubbed part is less than 3 times of the unrubbed part

[0214] △: The peeling force of the rubbed part is 3 times or more and less than 10 times that of the unrubbed part

[0215] ×: The peeling force of the rubbed part is 10 times or more that of the unrubbed part

[0216] (Water adhesion energy of release layer)

[0217] The water adhesion energy of the release film was measured using a fully automatic contact angle meter DM-701 manufactured by Kyowa Interface Science Co., Ltd. Specifically, the release film was made to be stationary (i.e. fixed) on a flat glass substrate at a temperature of 23 degrees and a humidity of 50%, and then a 7.0 μl drop of water was added to the surface of the release layer of the release film with the glass substrate tilted at 0 degrees (i.e. horizontal). After the drop was stationary for 3 seconds, the glass substrate was tilted at a speed of 1 degree / second, and the adhesion energy (mJ / m) was calculated using the following formula from the droplet's sliding angle, landing radius, droplet mass, and gravitational acceleration when the droplet's endpoint left the stationary position. 2 ).

[0218] E=(m×g×sinα) / (2×π×r)

[0219] In this formula, E is the adhesion energy, m is the mass of the droplet, g is the gravitational acceleration, α is the sliding angle, and r is the landing radius.

[0220] (Si element ratio on the outermost surface of the release layer)

[0221] The Si element ratio of the outermost surface of the release layer of the release film was measured by electron spectroscopy for chemical analysis (ESCA). The device used was K-Alpha + (manufactured by Thermo Fisher Scientific). The details of the measurement conditions are as follows. The device is used to perform narrow scans of the five elements C, O, N, S, and Si on the surface of the release layer, and the Si element ratio (at%) is calculated by the following formula. That is, here, the Si element ratio is the ratio (at%) of Si in the five elements C, O, N, S, and Si.

[0222] Si element ratio (at%) = {Si / (C+O+N+S+Si)}×100

[0223] It should be noted that, during the analysis, background removal was performed by the Shirley method. The surface Si element ratio is the average value of the measurement results at three or more locations.

[0224] Measurement conditions

[0225] Excitation X-ray: Monochromatized Al Ka ​​ray

[0226] X-ray output: 12kV, 6mA

[0227] Photoelectron separation angle: 90°

[0228] Spot size: 400mm f (about)

[0229] Pass energy: 50eV

[0230] Step size: 0.1eV

[0231] <Example 1>

[0232] Adhesion-imparting agent S1 (OSAKA SODACO., LTD. AD-032 diallylcyclohexane resin with a weight average molecular weight of 24,000 containing a polymer represented by formula C1) was dissolved in toluene so that the solid content concentration was 30%, and adhesion-imparting agent liquid A1 was prepared. Coating liquid M1 to which adhesion-imparting agent liquid A1 was added so that the solid content ratio relative to the heat addition type silicone resin (DOWSIL LTC750A manufactured by Dow Toray Co., Ltd. with a solid content concentration of 30%) was 20% (i.e., the solid content ratio of adhesion-imparting agent S1 relative to the heat addition type silicone resin) was prepared.

[0233] (Coating liquid M1)

[0234]

[0235] The coating liquid M1 was applied to one side (specifically, the corona-treated side) of a polyester film (TOYOBO ESTER Film E5100, 50 μm thick, single-sided corona-treated product manufactured by Toyobo Co., Ltd.) using a reverse gravure plate so that the coating thickness after drying was 50 nm. Then, the processing speed was adjusted so that the film entered the first drying oven after 0.5 seconds, and the heat drying and the curing of the release layer were continuously performed at the first drying oven temperature of 120° C. and the second drying oven temperature of 160° C. to obtain a release film.

[0236] <Example 2>

[0237] Adhesion imparting agent S2 (DAP-K manufactured by OSAKASODACO., LTD., a polymer having a structure represented by formula C2 and a weight average molecular weight of 50,000, a diallyl phthalate resin) was dissolved in toluene at a solid content concentration of 30% to prepare adhesion imparting agent liquid A2. Coating liquid M2 was prepared to which adhesion imparting agent liquid A2 was added at a solid content ratio of 20% relative to a heat addition type silicone resin (DOWSIL LTC750A manufactured by Dow Toray Co., Ltd., solid content concentration 30%). A release film was prepared by the same method as in Example 1 except that coating liquid M2 was used instead of coating liquid M1.

[0238] (Coating liquid M2)

[0239]

[0240] <Example 3>

[0241] Adhesion imparting agent S3 (ISODAP manufactured by OSAKASODACO., LTD., a polymer having a structure represented by formula C3 and containing diallyl phthalate resin having a weight average molecular weight of 20,000) was dissolved in toluene at a solid content concentration of 30% to prepare adhesion imparting agent liquid A3. Coating liquid M3 was prepared to which adhesion imparting agent liquid A3 was added at a solid content ratio of 20% relative to a heat addition type silicone resin (DOWSIL LTC750A manufactured by Dow Toray Co., Ltd., solid content concentration 30%). A release film was prepared by the same method as in Example 1 except that coating liquid M3 was used instead of coating liquid M1.

[0242] (Coating liquid M3)

[0243]

[0244]

[0245] <Example 4>

[0246] Coating liquid M4 was prepared by adding adhesion imparting agent liquid A1 to a heat addition type silicone resin (DOWSIL LTC750A manufactured by Dow Toray Co., Ltd., solid content concentration 30%) to give a solid content ratio of 10%. A release film was prepared in the same manner as in Example 1 except that coating liquid M4 was used instead of coating liquid M1.

[0247] (Coating liquid M4)

[0248]

[0249] <Comparative Example 1>

[0250] A release film was produced in the same manner as in Example 1 except that a coating liquid M5 having the following composition was used instead of the coating liquid M1.

[0251] (Coating liquid M5)

[0252]

[0253]

[0254] <Comparative Example 2>

[0255] A coating liquid M6 was prepared in which an adhesion-imparting agent, specifically a reaction product of vinyl triacetoxysilane and glycidoxypropyl trimethoxysilane (SD7200 manufactured by Dow Toray Co., Ltd., solid content concentration 90%) was added to a heat-addition type silicone resin (DOWSIL LTC750A manufactured by Dow Toray Co., Ltd., solid content concentration 30%) so as to have a solid content ratio of 10%. A release film was prepared in the same manner as in Example 1 except that the coating liquid M6 was used instead of the coating liquid M1.

[0256] (Coating liquid M6)

[0257]

[0258] <Comparative Example 3>

[0259] Diallyl phthalate (DAP) monomer (diallyl phthalate manufactured by Tokyo Chemical Industry Co., Ltd.) as an adhesion-imparting agent was dissolved in toluene so that the solid content concentration was 30%, and adhesion-imparting agent liquid A4 was prepared. Coating liquid M7 was prepared in which adhesion-imparting agent liquid A4 was added so that the solid content ratio was 20% relative to a heat addition type silicone resin (DOWSIL LTC750A manufactured by Dow Toray Co., Ltd., solid content concentration 30%). A release film was prepared by the same method as in Example 1 except that coating liquid M7 was used instead of coating liquid M1.

[0260] (Coating liquid M7)

[0261]

[0262] <Comparative Example 4>

[0263] Adhesion-imparting agent 4 (UVAD-091 phthalate resin without vinyl group, weight average molecular weight 3000, manufactured by OSAKA SODA CO., LTD.) was dissolved in toluene so that the solid content concentration was 30%, and adhesion-imparting agent liquid A5 was prepared. Coating liquid M8 was prepared in which adhesion-imparting agent liquid A5 was added so that the solid content ratio was 20% relative to the heat addition type silicone resin (DOWSIL LTC750A manufactured by Dow Toray Co., Ltd., solid content concentration 30%). A release film was prepared by the same method as in Example 1 except that coating liquid M8 was used instead of coating liquid M1.

[0264] (Coating liquid M8)

[0265]

[0266] [Table 1]

[0267]

[0268] In Table 1, the solid content ratio is the ratio of the solid content mass of the adhesion-imparting agent to the solid content mass of the thermal addition type silicone resin. In Table 1, the oblique lines indicate that the weight average molecular weight was not measured. That is, the weight average molecular weight of SD7200 was not measured.

[0269] The release films using the adhesion-imparting agent S1 (AD-032), the adhesion-imparting agent S2 (DAP-K), and the adhesion-imparting agent S3 (ISODAP) have higher water adhesion than the release films using no adhesion-imparting agent (refer to Examples 1 to 4 and Comparative Example 1). Therefore, the release films using these adhesion-imparting agents (specifically, adhesion-imparting agents S1, S2, and S3) can reduce the degree of depression that may occur when a liquid fluid such as a ceramic slurry is applied to the release layer of the release film, or suppress the occurrence of depression.

[0270] Compared with the release film without any adhesion-imparting agent, the change ratio when rubbed off after wet heat treatment (i.e., peeling force of the rubbed part / peeling force of the unrubbed part) of the release film using adhesion-imparting agent S1 (AD-032), adhesion-imparting agent S2 (DAP-K), and adhesion-imparting agent S3 (ISODAP) is close to 1.0 (refer to Examples 1 to 4 and Comparative Example 1). The increase in the change ratio when rubbed off after wet heat treatment is caused by the detachment of the release layer (specifically, the detachment of the release layer from the polyester film), so the release film using these adhesion-imparting agents (specifically, adhesion-imparting agents S1, S2, S3) can be evaluated as the release layer is not easy to detach from the polyester film compared with the release film without any adhesion-imparting agent. That is, it can be evaluated that the adhesion between the release layer and the polyester film is improved by using these adhesion-imparting agents (specifically, adhesion-imparting agents S1, S2, S3).

[0271] The tape peeling force of the release film using the adhesion-imparting agent S1 (AD-032), the adhesion-imparting agent S2 (DAP-K), and the adhesion-imparting agent S3 (ISODAP) is not significantly different from the tape peeling force of the release film not using any adhesion-imparting agent (refer to Examples 1 to 4 and Comparative Example 1).

[0272] On the other hand, the water adhesion energy of the release film using SD7200 (the reaction product of vinyl triacetoxysilane and glycidoxypropyl trimethoxysilane) as the adhesion-imparting agent is the same as the water adhesion energy of the release film using no adhesion-imparting agent (refer to Comparative Examples 1 and 2). Regarding the change ratio of wiping after wet heat treatment, which is an indicator of adhesion, the change ratio is close to 1.0 by SD7200, that is, the adhesion is improved (refer to Comparative Examples 1 and 2), but the improvement in adhesion achieved by SD7200 is less than the improvement in adhesion achieved by adhesion-imparting agents S1, S2, and S3 (refer to Comparative Examples 1 and 2 and Examples 1 to 4).

[0273] The water adhesion energy of the release film using DAP monomer as an adhesion-imparting agent is higher than that of the release film not using any adhesion-imparting agent (refer to Comparative Examples 1 and 3), but the improvement of water adhesion energy by DAP monomer is smaller than that by adhesion-imparting agents S1, S2, and S3 (refer to Comparative Examples 1 and 3, Examples 1 to 4). Regarding the change ratio of rubbing after wet heat treatment, which is an indicator of adhesion, although the change ratio is reduced by DAP monomer, that is, the adhesion is improved (refer to Comparative Examples 1 and 3), the improvement of adhesion by DAP monomer is smaller than that by adhesion-imparting agents S1, S2, and S3 (refer to Comparative Examples 1 and 3 and Examples 1 to 4). Regarding the peelability, the tape peeling force of the release film using DAP monomer is much higher than that of the release film not using any adhesion-imparting agent (refer to Comparative Examples 1 and 3). The Si element ratio of the release film using DAP monomer is significantly smaller than the Si element ratio of the release film not using any adhesion-imparting agent, so it is believed that the DAP monomer is transferred to the surface of the release layer, thereby causing heavy peeling in the release film using DAP monomer (refer to Comparative Examples 1 and 3).

[0274] The change ratio (specifically, the change ratio after wiping off after wet heat treatment, which is an indicator of adhesion) of the release film using UVAD-091 (phthalate resin without vinyl group) as the adhesion-imparting agent is smaller than that of the release film without any adhesion-imparting agent (refer to Comparative Examples 1 and 4), but the improvement of adhesion achieved by UVAD-091 is smaller than that achieved by adhesion-imparting agents S1, S2, and S3 (refer to Comparative Examples 1 and 4 and Examples 1 to 4). Regarding the peelability, the tape peeling force of the release film using UVAD-091 is significantly higher than that of the release film without any adhesion-imparting agent (refer to Comparative Examples 1 and 4). It should be noted that regarding the water adhesion energy, the water adhesion energy of the release film using UVAD-091 is higher than the water adhesion energy of the release film using no adhesion-imparting agent (refer to Comparative Examples 1 and 4), and is at the same level as the water adhesion energy of the release film using adhesion-imparting agents S1, S2, and S3 (refer to Comparative Example 4 and Examples 1 to 4).

[0275] Industrial Applicability

[0276] The present invention relates to a release film and therefore has industrial applicability.

Claims

1. A release film comprising a polyester film and a release layer, The release layer is a layer formed by curing a silicone composition containing addition-curable silicone. The silicone composition contains a resin having neither a silicon atom nor a nitrogen atom in a molecule and containing a plurality of alkenyl groups and a plurality of rings in the molecule, The rings are each independently at least one selected from the group consisting of a monovalent aromatic ring, a divalent aromatic ring, a monovalent aliphatic ring, and a divalent aliphatic ring.

2. The release film according to claim 1, wherein The alkenyl group is an allyl group.

3. The release film according to claim 1, wherein The rings are each independently at least one selected from the group consisting of a phenylene group, a naphthylene group, a cyclopentylene group, and a cyclohexylene group.

4. The release film according to claim 1, wherein The resin includes a plurality of ester bonds in the molecule.

5. The release film according to claim 1, wherein The resin contains a plurality of structural units represented by the following formula in the molecule, Each of the plurality of Xs is independently at least one selected from the group consisting of a phenylene group, a naphthylene group, a cyclopentylene group, and a cyclohexylene group.

6. The release film according to claim 1, wherein The weight average molecular weight of the resin is 4000 or more. 7 . The release film according to claim 1 , which is used for producing a ceramic green sheet.

Citation Information

Patent Citations

  • Mold release film

    CN107428135A

  • Mold release film

    CN109789678A

  • Mold release film and laminate

    CN111051061A

  • Epoxy resin, method for producing same, curable epoxy resin composition, cured product, preg, insulation sheet, and laminate

    CN111978511A

  • Release agent composition for metal mold, releasability enhancing method and manufacturing method for molded article using them

    JP2003285335A